Genomic sites of topoisomerase II activity determined by comparing DNA breakage enhanced by three distinct poisons. - Borgnetto, M.E.; Tinelli, S.; Carminati, L.; Capranico, G. (Journal of Molecular Biology, 1999)
To define the sites of topoisomerase II activity in two genomic regions of Drosophila melanogaster Kc cells, we have investigated in vivo DNA cleavage sites stimulated by three poisons with diverse sequence specificity, clerocidin, VM-26 and dh-EPI (an anthracycline analog). DNA cleavage was studied by PFGE (pulse-field gel electrophoresis), standard gel electrophoresis, and by genomic primer extension. Poisons stimulated specific intensity patterns of cleavage in the two genomic regions studied. At the centromeric satellite III DNA, fragments of about 270-310 and 385-430 kb could be detected specifically after treatment with clerocidin, suggesting a complex DNA loop organisation, which may correspond with a centromere-specific higher-order chromatin structure. Clerocidin-dependent DNA fragmentation was detectable by PFGE but not by standard agarose gel electrophoresis; while VM-26-dependent cleavage was detected with either method, dh-EPI was ineffective at this locus. Thus, clerocidin DNA cleavage sites were rarer than those of VM-26 at the satellite locus. In the histone H2A-H2B intergenic region, clerocidin and dh-EPI stimulated cleavage whereas VM-26 was only weakly effective. Some clerocidin cleavage sites did not undergo spontaneous reversion, indicating that this agent can stimulate irreversible cleavage in vivo. Direct genomic sequencing showed that many clerocidin and dh-EPI sites, although distinct, mapped to the transcription start and to the proximal promoter of the H2A gene, suggesting that the region is highly accessible to topoisomerase II. Thus, the enzyme may play a role in maintaining a highly accessible chromatin structure under normal cell growth conditions, possibly mediated by specialised protein complexes. This study demonstrates that the use of distinct poisons greatly improves the definition of genomic sites of topoisomerase II activity.